PROFIL PEMECAHAN MASALAH SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL SISWA KELAS VIII SMPN 21 PALU DITINJAU DARI KEMAMPUAN MATEMATIKA - Nur Padila Susanti; Ibnu Hadjar; Pathuddin Pathuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to obtain a problem-solving profile of a two-variable linear equation system for grade VIII students of SMP Negeri 21 Palu reviewed from the student’s mathematical abilities based on Polya steps. This study uses a qualitative method with a qualitative descriptive approach based on the problem-solving steps proposed by Polya. The results of the study showed that the subjects used in this study were three students, namely students with high mathematical ability (ZN), students with moderate mathematical ability (LT), and students with low mathematical ability (KB). The results of the study showed that subjects who had high, medium and low mathematical abilities in solving SPLDV mathematical problems were as follows: (1) in understanding problems, subjects with high mathematical abilities and were reading problems repeatedly, as well as their knowledge of "statement" sentences and "question" sentences. In contrast to subjects with low mathematical skills, they can identify the information available with their knowledge of "statement" sentences and "question" sentences, but subjects with low ability cannot understand every information in the problem even though they have read the problem repeatedly, (2) in planning problem solving, subjects with high mathematical ability and have a solution plan that The same is by using a combined method between elimination and substitution. In contrast to subjects with low mathematical ability who do not have a single mathematical solution plan at all, (3) in carrying out the problem-solving plan, subjects with high and medium mathematical ability can apply problem-solving strategies according to what has been previously planned, in contrast to subjects with low mathematical ability who do not solve problems because they cannot plan problem solving, (4) In re-examining the results of problem solving, the subject with high mathematical ability re-examines the results of his work by re-examining the results step by step of each process to find the answer. Furthermore, subjects with medium and low mathematical abilities do not re-examine their work because the subject cannot solve the given problem.